Citicoline: A Review of Analytical Methods: Citicoline: A Review of Analytical Methods - Bhardwaj, Kiran (International Journal of Pharmaceutical & Biological Archive, 2018)
Citicoline is a nootropic agent. It is used in the treatment of brain insufficiency and other neurological disorders such as brain stroke, trauma, and Parkinson’s disease. This review article represents summarized results of published analytical methods in the literature for the determination of citicoline in biological and pharmaceutical formulations. Various techniques such as spectrophotometry, liquid chromatography (LC), high-performance LC, ultra performance LC, gas chromatography, nuclear magnetic resonance, and hydrophilic interaction LC method were reported.